2012
DOI: 10.3892/or.2012.2052
|View full text |Cite
|
Sign up to set email alerts
|

miR-183 as a molecular and protective biomarker for cancer in schizophrenic subjects

Abstract: Previous studies have suggested that schizophrenia is associ-ated with a reduced risk of cancer. Genes that are involved in cell cycle regulation seem to have additional functions in post-mitotic neurons involved in neuronal migration and synaptic plasticity. MicroRNAs (miRNAs) play a dominant role in the regulation of gene expression in the central nervous system (CNS). Due to their involvement in a large number of CNS pathways, miRNAs pose as appeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…miR-183 is a miRNA that has never been correlated with neurodegenerative diseases in the past, with the exception of a recent study where the possible suppressive role of miR-183 in the neurobiological pathways involved in schizophrenia was highlighted [15]. Mir183 has recently been implicated in modulation of different apoptotic and autophagic stages through regulation of apoptosis and autophagy-related genes [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…miR-183 is a miRNA that has never been correlated with neurodegenerative diseases in the past, with the exception of a recent study where the possible suppressive role of miR-183 in the neurobiological pathways involved in schizophrenia was highlighted [15]. Mir183 has recently been implicated in modulation of different apoptotic and autophagic stages through regulation of apoptosis and autophagy-related genes [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the expression levels of miR-183 and thymidine kinase (TK) 1 (TK1) in the peripheral blood of malignant carcinoma patients were significantly increased, suggesting their potential as serological markers for cancer diagnosis [9][10][11][12]. In this study, the expression levels of serum miR-183 https://doi.org/10.1515/biol-2017-0029…”
Section: Introductionmentioning
confidence: 73%
“…Various studies have proved prominent roles of miRNAs in many physiological and pathological processes, and miRNAs could be a diagnostic and prognostic biomarker for various diseases such as cancer and CNS diseases including schizophrenia (Rao et al, 2013 ). Rizos et al ( 2012 ) found that miR-183 was upregulated in the group of persons with schizophrenia without cancer but was almost undetectable in the group of persons with schizophrenia with a solid tumor. Therefore, they proposed that miR-183 could be a protective biomarker for cancer in schizophrenic subjects (Rizos et al, 2012 ).…”
Section: The Similar Mechanisms Involved In Glioma Tumorigenesis and mentioning
confidence: 99%